Antibacterial activity in vitro investigation of eucheuma cottonii extract from aru islands against pathogenic bacteria - Yunita, Melda; Warella, Juen Carla; Astuty, Eka; Ohiwal, Morgan; Alimudi, Saiful (JPBIO (Jurnal Pendidikan Biologi), 2024)
Red algae Eucheuma cottonii is one of the potential marine biodiversity that provides added value in the pharmaceutical and cosmetic fields and is known to have antibacterial compounds. Research focusing on the potential of E. cottonii as an antibacterial is still limited, particularly when it comes to the Aru Islands. This study aimed to measure the antibacterial activity of E. cottonii against pathogenic bacteria including E. coli and S. aereus at several concentrations and to determine the best concentration for inhibiting these two pathogenic bacteria. The study was true experimental laboratory research with a post-test-only controlled group design. Antibacterial tests using the disc diffusion method and phytochemical tests were carried out. This study revealed that E. cottonii could be able to inhibit S. aureus ranging from 0.27±0.03 – 2.1±0.14 at a concentration of 50%-100%, and 0.17±0.05 – 0.45 ± 0.03 against E. coli at a concentration of 80-100%. Meanwhile, saponins and flavonoids were two bioactive compounds found through phytochemical testing. The study concluded that the n-hexane extract of E. cottonii was able to inhibit the growth of E. coli and S. aureus, even with a weak inhibition category. This study recommends that improvements are needed in the E. cottonii extraction process to maximize the antibacterial properties of E. cottonii.